The Relationship Between Work Motivation and Job Satisfaction and the Organizational Behavior of Employees at PT Glostar Indonesia - Umar Mansur; Safira Rifa Fadillah (Westscience Press, 2026)
This study aims to analyze the relationship between work motivation and job satisfaction on the organizational behavior of PT Glostar Indonesia employees. The approach used in this study is a quantitative approach with descriptive and associative research types. Data were obtained by distributing questionnaires to PT Glostar Indonesia employees as research respondents. The sampling technique was carried out using the probability sampling method, while the data analysis technique used descriptive statistical analysis and multiple linear regression with the help of SPSS software. The results of the study indicate that work motivation has a positive and significant effect on employee organizational behavior. Job satisfaction is also proven to have a positive and significant effect on employee organizational behavior. In addition, simultaneously, work motivation and job satisfaction have a significant effect on employee organizational behavior at PT Glostar Indonesia. These findings indicate that increasing work motivation and job satisfaction can encourage the formation of positive, productive organizational behavior and support the achievement of company goals. Based on these research results, it can be concluded that work motivation and job satisfaction are important factors that need to be considered by PT Glostar Indonesia management in an effort to improve employee organizational behavior sustainably.